2021
DOI: 10.7759/cureus.12814
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pre-existing Ventriculoperitoneal Shunt in Posterior Vault Distraction for Lambdoid Craniosynostosis: A Case Report and Technical Note

Abstract: Posterior vault distraction osteogenesis (DO) is an emerging treatment option for craniosynostosis. Operative nuances detailing surgical management are being described with increasing use and experience. In this article, we discuss the surgical management of an 8-month-old male with a ventriculoperitoneal shunt (VPS) diagnosed with bilateral lambdoid craniosynostosis and Chiari I malformation. The patient underwent successful bilateral posterior fossa DO without surgical re-implantation of the shunt. Pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Some of the systematically reviewed articles were published before the advent of distraction osteogenesis, but the predominance of cranial vault remodeling in SRC treatment may be partly explained by remarks in some case reports that surgeons would have to contend with potential shunt movement and the complications of installing hardware around the shunt. 20,22 In addition to those present in every systematic review, our study did have several limitations. First, the true incidence of SRC may also be lower than our reported pooled rate as we excluded studies discussing complications of patients shunted for hydrocephalus, but without a single case of SRC.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Some of the systematically reviewed articles were published before the advent of distraction osteogenesis, but the predominance of cranial vault remodeling in SRC treatment may be partly explained by remarks in some case reports that surgeons would have to contend with potential shunt movement and the complications of installing hardware around the shunt. 20,22 In addition to those present in every systematic review, our study did have several limitations. First, the true incidence of SRC may also be lower than our reported pooled rate as we excluded studies discussing complications of patients shunted for hydrocephalus, but without a single case of SRC.…”
Section: Discussionmentioning
confidence: 96%
“…In the included studies, the sagittal suture was most involved, cited to be the site of fusion in 88% of single-involvement cases, and was also fused in 98% of cases when more than one suture was involved. Other reports of SRC in the literature share this prevalence of sagittal closure and it is also known to be characteristic of all-cause craniosynostosis 1,18,20,23–25 . Whether this is related to the site of shunt placement was addressed by Golinko et al, 1 who found that there is no relationship between the location of shunt placement and involved sutures.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations